2007
DOI: 10.1097/bpo.0b013e31802b7183
|View full text |Cite
|
Sign up to set email alerts
|

The Contralateral Foot in Children With Unilateral Clubfoot

Abstract: The unaffected contralateral side of patients with unilateral clubfeet has sometimes been taken as control in foot pressure measurement studies. However, it has never been shown that the pressure pattern under the contralateral foot is similar to a normal foot. Sixteen patients with unilateral clubfoot and 110 normal subjects took part in this study. All participants were aged from 4 to 8 years. Studies comprised clinical examination and foot pressure measurements in barefoot walking. Evaluations of the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
2
26
1
Order By: Relevance
“…Our results are consistent with these sorts of asymmetries, showing differences only in peak pressure measurement between the two feet. Similar to Favre et al [8], we found the unaffected foot had increased peak pressure for the areas M1, M8, and M10, representing the area of the medial hindfoot, hallux, and third to fifth toe, with decreased pressure in the lateral midfoot area. There may also be mechanical influence of the soft tissue around the heel pad on hindfoot peak pressure [18], resulting in decreased pressure values with increasing tissue thickness.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our results are consistent with these sorts of asymmetries, showing differences only in peak pressure measurement between the two feet. Similar to Favre et al [8], we found the unaffected foot had increased peak pressure for the areas M1, M8, and M10, representing the area of the medial hindfoot, hallux, and third to fifth toe, with decreased pressure in the lateral midfoot area. There may also be mechanical influence of the soft tissue around the heel pad on hindfoot peak pressure [18], resulting in decreased pressure values with increasing tissue thickness.…”
Section: Discussionsupporting
confidence: 84%
“…Mean peak pressures were reduced (p \ 0.005) in all hindfoot and forefoot areas (M1, 2, 5, 6,7,8,9,10) in the clubfoot group compared with those of the control group (Table 1) (Fig. 4).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Extensive studies have surveyed children's locomotion by investigating the biomechanics of walking [2][3][4][5] . However, little scientific study has studied other functional abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Motion analysis in congenital CF children is applied to understand the mechanics of that dysfunction, for the affected and unaffected sides [2][3][4][5] . To improve rehabilitation procedures for CF, gait and other motor skills should be evaluated.…”
Section: Introductionmentioning
confidence: 99%